2009
DOI: 10.1002/jor.21008
|View full text |Cite
|
Sign up to set email alerts
|

An internal locking plate to study intramembranous bone healing in a mouse femur fracture model

Abstract: In most murine fracture models, the femur is stabilized by an intramedullary implant and heals predominantly through endochondral ossification. The aim of the present study was to establish a mouse model in which fractures heal intramembranously. Femur fractures of 16 SKH-mice were stabilized by an internal locking plate. Femur fractures of another 16 animals were stabilized by an intramedullary screw. Bone repair was analyzed by radiographic, biomechanical, and histological methods. At 2 weeks, histological a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
31
1
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 57 publications
(34 citation statements)
references
References 31 publications
1
31
1
1
Order By: Relevance
“…During the last few years, a considerable number of implants for fracture stabilization in mice have been developed, including locking nails (Holstein et al, 2007), intramedullary screws , locking plates (Histing et al, 2010), pinclip devices and external fixators (Cheung et al, 2003). Our results indicate that further studies are required to characterize the effect of these different osteosynthesis techniques on the mouse gait and motion pattern recovery.…”
Section: Discussionmentioning
confidence: 73%
“…During the last few years, a considerable number of implants for fracture stabilization in mice have been developed, including locking nails (Holstein et al, 2007), intramedullary screws , locking plates (Histing et al, 2010), pinclip devices and external fixators (Cheung et al, 2003). Our results indicate that further studies are required to characterize the effect of these different osteosynthesis techniques on the mouse gait and motion pattern recovery.…”
Section: Discussionmentioning
confidence: 73%
“…[1][2][3][4][5] Because bone is highly vascularized, angiogenesis plays an extremely important role in bone formation during both bone development and fracture healing. [6,7] Previous studies have demonstrated that the angiogenic and osteogenic factors associated with the proteins of vascular endothelial growth factor (VEGF) and cysteine-rich 61 (CYR61) are involved in the process of fracture healing, [6][7][8][9] and that reduced vascularity at the fracture site is one of the most significant risk factors for delayed fracture healing.…”
mentioning
confidence: 99%
“…[16][17][18][19][20][21] The challenge in experimental murine trauma modeling is long term investigation, as fracture fixation techniques in mice, can be complex and not easily reproducible. [22][23][24][25][26][27][28][29][30] This pseudofracture model, an easily reproduced trauma model, overcomes these difficulties by immunologically mimicking an extremity fracture environment, while allowing freedom of movement in the animals and long term survival without the continual, prolonged use of anaesthesia. The intent is to recreate the features of long bone fracture; injured muscle and soft tissue are exposed to damaged bone and bone marrow without breaking the native bone.…”
mentioning
confidence: 99%